3D lithium metal embedded within lithiophilic porous matrix for stable lithium metal batteries. (July 2017) - Jin, Chengbin; Sheng, Ouwei; Luo, Jianmin; Yuan, Huadong; Fang, Cong; Zhang, Wenkui; Huang, Hui; Gan, Yongping; Xia, Yang; Liang, Chu; Zhang, Jun; Tao, Xinyong
Abstract: Lithium metal as an attractive anode material has been widely used in the advanced energy storage technology such as lithium-sulfur and lithium-air batteries. However, suffering from the uncontrollable deposition, growth of lithium dendrite and the serious volume change within cycling process, the commercial application of lithium anode is impeded by the safety hazards and limited span-life. Here, we demonstrate a kind of bamboo-derived 3D hierarchical porous carbon decorated by ZnO quantum dots which can serve as a lithiophilic scaffold for dendrite-free Li metal anode. This carbon scaffold is stable against the serious volumetric change during cycles. In addition, the 3D porous scaffold can reduce the effective local current density. Most importantly, the lithiophilic ZnO quantum dots within the carbon can be used to induce lithium deposition. Notably, lithium metal up to 131 mAh cm −2 can be confined within ZnO@HPC, achieving acceptable volume expansion, considerable reduction in overpotential and effective dendrite suppression. Thus, 3D Li within ZnO@HPC scaffold could exhibit better capability and much lower voltage hysteresis when compared with Li foil in cells paired with LiCoO2 . The function of the ZnO decorated 3D hierarchical porous carbon scaffold might provide innovative insights into the design principles for metallic lithium anodes. Graphical abstract: A subtle 3D porous carbon with the uniformly anchored ZnO quantum dots as the inducing agent for lithium deposition has been designed as promising matrix for dendrite-free lithium metal anode. Highlights: Lithiophilic ZnO quantum dots decorated hierarchical porous carbon was prepared. The stripping/plating behavior of Li within the ZnO@HPC scaffold was investigated. Dendrite-free lithium metal anode was achieved within the ZnO@HPC matrix. 3D Li within ZnO@HPC delivers much better electrochemical performance.